2001
DOI: 10.1111/j.1467-842x.2001.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight changes in the pilot phase of the Strong Women Strong Babies Strong Culture Program in the Northern Territory

Abstract: Objective : The Strong Women Strong Babies Strong Culture Program had specific goals to increase infant birthweights by earlier attendance for antenatal care and improved maternal weight status. Starting in August 1993, Aboriginal women in three pilot communities worked with pregnant women in a program that emphasised both traditional practices and Western medicine. Method : Two sources of data were used to examine different aspects of program effects. Results : Data from the NT Midwives Collection shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 11 publications
3
43
0
Order By: Relevance
“…d 'Espaignet et al (2003) evaluated the effect of the Strong Women, Strong Babies, Strong Culture program (SWSBSC), which operates in remote Aboriginal communities in the NT. Findings of an earlier evaluation (Mackerras 2001) were also reported in this paper. SWSBSC activated traditional relationships where older Aboriginal women cared for pregnant women, encouraging them to visit medical clinics and providing advice about nutrition (including bush foods).…”
Section: Birthingsupporting
confidence: 54%
“…d 'Espaignet et al (2003) evaluated the effect of the Strong Women, Strong Babies, Strong Culture program (SWSBSC), which operates in remote Aboriginal communities in the NT. Findings of an earlier evaluation (Mackerras 2001) were also reported in this paper. SWSBSC activated traditional relationships where older Aboriginal women cared for pregnant women, encouraging them to visit medical clinics and providing advice about nutrition (including bush foods).…”
Section: Birthingsupporting
confidence: 54%
“…Preterm birth and low birth weight are leading causes of health problems that may persist through childhood and into adolescence (Lobel et al 2008;Mackerras 2000). Hayes et al (2010) conducted a study examining the impact that social stressors have on obstetric outcomes in a sample of 92 Aboriginal women from Queensland, Australia.…”
Section: Stress In Pregnancy and Infant Outcomesmentioning
confidence: 99%
“…43 The association between pregnancy-induced hypertension and PTB was marginally significant in our study whereas a larger Queensland study in Indigenous women found it to be a more important predictor (AOR: 4. 44 A recent evaluation found that although the program was still recognised as a 'flagship program,' there were substantial challenges in its provision and sustainability impeding it from reaching its potential. 45 This program was not operating in one of our study settings and had been reduced from its former size in the other.…”
Section: Sv Kildea Et Al / Women and Birth XXX (2016) Xxx-xxxmentioning
confidence: 99%